2016
DOI: 10.1002/pro.2976
|View full text |Cite
|
Sign up to set email alerts
|

The yeast transcription elongation factor Spt4/5 is a sequence‐specific RNA binding protein

Abstract: The heterodimeric transcription elongation factor Spt4/Spt5 (Spt4/5) tightly associates with RNAPII to regulate both transcriptional elongation and co-transcriptional pre-mRNA processing; however, the mechanisms by which Spt4/5 acts are poorly understood. Recent studies of the human and Drosophila Spt4/5 complexes indicate that they can bind nucleic acids in vitro. We demonstrate here that yeast Spt4/5 can bind in a sequence-specific manner to single stranded RNA containing AAN repeats. Furthermore, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…Indeed, there is increasing evidence that RNArelated activities are important for processes occurring on chromatin templates [45,46]. For example, RNA-binding activity has been recently demonstrated for the DSIF (Spt4/Spt5) factor of RNA polymerase II pausing [47].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is increasing evidence that RNArelated activities are important for processes occurring on chromatin templates [45,46]. For example, RNA-binding activity has been recently demonstrated for the DSIF (Spt4/Spt5) factor of RNA polymerase II pausing [47].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the Spt4/5 complex may play a distinct role from Spt6 in transcription by Pol II. Since these early studies, many additional studies have characterized the role of the Spt4/5 complex in transcription by Pol II, and the most widely accepted hypothesis is that this complex may help the polymerase to overcome pausing (especially promoter-proximal pausing), traverse nucleosomes, and aid in nascent RNA processing [ 25 , 26 , 27 , 28 ]. Interestingly, Spt4/5 is the only known transcription factor that is conserved throughout all domains of life (with the bacterial homolog of SPT5 being nusG ), emphasizing the importance of this factor in transcription in potentially all organisms [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes known to be highly susceptible to inhibition via promoter-proximal pausing are those that are immediately activated in response to stress and extracellular signals such as heat shock and proinflammatory genes (Boehm et al, 2003;Diamant and Dikstein, 2013;Missra and Gilmour, 2010;Rougvie and Lis, 1990;Wu et al, 2003). During elongation, Spt5 has the ability to stabilize Pol II on the DNA template by interacting with upstream sequences and with RNA (Bernecky et al, 2016;Blythe et al, 2016;Crickard et al, 2016;Hirtreiter et al, 2010;Klein et al, 2011;Martinez-Rucobo et al, 2011). This activity was recently implicated in maintaining high transcriptional speed on long mRNAs (Fitz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%